Peran Mediasi FinTech antara Literasi Keuangan dan Pengelolaan Arus Kas Mahasiswa - Barnabas Tridig; Nelvina Margery; Nelsi Cerdik Intani Bate'e; Angel Grace Nababan; Gracia Maharani Sepang; , Lenni Putri Telaumbanua; Sisca Laura (Politeknik Ganesha Medan, 2026)
The development of financial technology (FinTech) has transformed personal finance management, but poor digital financial literacy (DFL) poses a threat to the effectiveness for the cash flow management (CFM) of university students. Researchers examined the effect of DFL in CFM by exploring role of i-FinTech Adoption (IFA) as a mediator, while controlling for the influences of gender and age. It addresses a gap in literature by proposing a mediation model that connects this trio of variables within the context specific to Indonesian students. A quantitative survey method was applied to 201 FinTech-user students from various Indonesian universities, using purposes and snowball sample sampling techniques. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, including bootstrapping and multi-group analysis. The results prove that DFL significantly positively influences CFM, both immediately and indirectly though IFA, after controlling for gender and age. The finding of partial mediation indicates that i-FinTech acts as a behavioral infrastructure that transforms knowledge into more disciplined financial practices. The research implications emphasize the need for a dual strategy: strengthening applied digital financial literacy education and developing educational FinTech features.